Polish Translation Studies in Action Concepts - Methodologies - Applications. A Reader - de Bończa Bukowski, Piotr; Heydel, Magdalena (Cross-Roads, 2019)
Translation Studies has been in action in the Polish humanities since 1930s. The book gathers the most important contributions from Polish translation scholars working in the context of Literary and Cultural Studies as well as Linguistics. The essays offer insights into the conceptualisation of translation, stylistics and poetics, history and anthropology of translation. Most of them are made available in English for the first time. The editors' introduction provides a panoramic backdrop for concepts, methodologies and applications. As part of the tendency to enlarge Translation Studies and include new contexts into its mainstream, this reader gives an overview of a rich area of translation scholarship from the centre of Europe, a crossroads of influences and traditions.